Dental anomalies in cleft lip and/or palate children at age 10 - a retrospective review across three cleft centres: Part 1. - Ezzeldin, Maryam; Gee, Samantha; Curtis, Jacob; Clark, Victoria J; Smallridge, Jacqueline; Collard, Mechelle (Springer Science and Business Media LLC, 2023)
Introduction Children with oral clefts often present with dental anomalies which can impact function, aesthetics and complicate the patient's dental treatment and needs. An understanding of potential anomalies, along with early recognition and planning, is thus essential for effective care.Aim This paper is the first in a two-part three-centre series. This paper will assess the dental anomalies identified in 10-year-old patients attending three cleft centres in the UK.Method Retrospective review was undertaken of the clinical notes of 10-year-old patients attending South Wales (SW), Cleft NET East (CNE) and West Midlands (WM) cleft units, for their ten-year audit record appointment in 2016/2017.Results In total, 144 patients were reviewed (SW = 42; CNE = 52; WM = 50). Dental anomalies were recorded for 80.6% of patients (n = 116).Discussion The review gives insight into the dental complexities of UK oral cleft patients. These patients require specialist paediatric dental input and intensive preventive regimes.Conclusion Shared care between cleft team specialists and general dental practitioners is important when providing holistic care for cleft patients.
Acknowledgements: The authorship would like to acknowledge and thank Renata Medeiros Mirra for her guidance in the statistical analysis of data and interpretation of findings.
Keywords: Humans; Child; Cleft Lip; Cleft Palate; Retrospective Studies; Dentists; Esthetics, Dental; Professional Role